Slovaropisje klasičnih jezikov na Slovenskem v 16. stoletju - Hriberšek, Matej (Slavia Centralis, 2020)
Lexicography of classical languages in Slovenia in the 16th centuryThe origins of classical language lexicography in Slovenia may be found in a few remnants from the Middle Ages and in the works by Slovene Protestant writers (Abecedarium, Otročja biblija, Ljubljanska začetnica, Register to Bible). However, the real beginning of Slovene lexicography is the work Dictionarium quatuor linguarum by Hieronymus Megiser.
Keywords: Classical languages; Latin; lexicography; Trubar; Megiser; protestants